Os professores e o conselho de escola: compromisso pedagógico democrático - Bioto Filho, Luiz Carlos (2013)
This Master s thesis aims to discuss the participation of teachers in the management of public schools prioritizing in this discussion, participation in the School Council. The study reflects on political foundations of democratic governance, the role of teachers is managed and on the instruments by which favors the participation. Management experiences were investigated in the public schools of the county school system Itaquaquecetuba (SP). Is scheduled and registered to both meetings and studies seeking date and relevant to the research and the practical training towards a political-pedagogical institutional culture topics agreement. The investigation came was inserted into instances of training, so. The proposals, due to insertion, were defining themselves according to directions and challenges discussed in commonly agreed areas planning, discussions, reviews. Reasons, this study will refer the record of intervention processes in schools, already discussed and made possible the agreed interfaces between the production of the dissertation and practice training in the Board of Education operates. The final consideration is that the School Board may rather be in a democratic, able to promote the distribution of power within the school, able to promote politicizing participation by involving teachers and all space.